Measuring, evaluating, and documenting social marketing impact - Truong, V. Dao; Dong, X. Dam; Saunders, Stephen Graham; Pham, Quynh; Nguyen, Hanh; Tran, Ngoc Anh (Journal of social marketing, 2021)
Purpose This paper aims to examine how social marketing intervention programmes to measure, evaluate and document social marketing impact. Design/methodology/approach A systematic review of 49 nutritional behaviour intervention programmes (2006–2020) was conducted. To examine the social marketing impact of the programmes, a logic model of social impact was used. The model comprises inputs (the resources used for an intervention programme), outputs (the direct products resulting from the use of resources), outcomes (short- to medium-term programme effects) and impacts (long-term programme effects on the individual, community or societal levels). Findings Most intervention programmes set the goal of encouraging their target audience to increase fruit and vegetable intake, choose healthy food items, drink less sugary beverages or consume low-fat diaries, while few others sought policy or systems change. Multiple criteria were used for impact evaluation (e.g. exposure and reach, changes in knowledge, awareness, attitudes, behaviours and body mass index). (Quasi) experiments were the most popular method used for impact measurement, followed by the pre-post model of impact. Positive changes were found in 33 programmes, often reported in terms of short-term outputs or outcomes. Long-term impact particularly on the broader societal level was not indicated. Originality/value This research offers a systematic review of how social marketing impact is measured, evaluated and documented. It also provides some guidance for social marketers on how to shift from a reductionist, behavioural outcome-focussed approach towards an “expansionist” impact approach that explicitly considers social marketing impacts on the quality of life of individuals, communities and societies.